2014
DOI: 10.1021/nl5016848
|View full text |Cite
|
Sign up to set email alerts
|

Controlled, Reversible, and Nondestructive Generation of Uniaxial Extreme Strains (>10%) in Graphene

Abstract: Theoretical calculations have predicted that extreme strains (>10%) in graphene would result in novel applications. However, up to now the highest reported strain reached ∼1.3%. Here, we demonstrate uniaxial strains >10% by pulling graphene using a tensile-MEMS. To prevent it from slipping away it was locally clamped with epoxy using a femtopipette. The results were analyzed using Raman spectroscopy and optical tracking. Furthermore, analysis proved the process to be reversible and nondestructive for the graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
65
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 43 publications
2
65
0
2
Order By: Relevance
“…For example, the uniaxial and biaxial strains larger than 10% have been achieved experimentally in graphene2930. Our simulations have demonstrated that the ultrathin GaAs film considered in this work can sustain high tensile strain (>10%) without the appearance of structural transition and bond breakage.…”
Section: Discussionmentioning
confidence: 52%
“…For example, the uniaxial and biaxial strains larger than 10% have been achieved experimentally in graphene2930. Our simulations have demonstrated that the ultrathin GaAs film considered in this work can sustain high tensile strain (>10%) without the appearance of structural transition and bond breakage.…”
Section: Discussionmentioning
confidence: 52%
“…13,21 Studies of the effect of biaxial strain on graphene are typically performed in the range 0.1%-1% of strain, 14,22-27 while uniaxial strain above 10% was reported. 28 Only one study 29 claims to achieve biaxial strains up to 20%. However, the corresponding Raman spectra show a shift of the 2D peak of just 10-20 cm -1 , which does not appear compatible with such a large strain.…”
mentioning
confidence: 99%
“…25 alternative promising approach consists in anchoring graphene layers to micro-electromechanical actuators. 27 More elaborated strain profiles, in particular those giving rise to a pseudomagnetic field, have been hard to demonstrate so far. Interesting experimental evidence has been put forward in the context of random nanobubbles 10 and fascinating results have been obtained in deformed artificial honeycomb structures mimicking the behavior of graphene.…”
mentioning
confidence: 99%